PERAN DISIPLIN KERJA DAN KOMPENSASI DALAM MEMPENGARUHI KINERJA ASN PADA RSUD BESUKI DENGAN MOTIVASI KERJA SEBAGAI VARIABEL INTERVENING - Cahyani, Diah Dwi Ari; Karnadi, Karnadi; Fandiyanto, Randika (Fakultas Ekonomi dan Bisnis, 2023)
Work discipline is the most importannt element in employee performance, in this case civil servants who work in goverment agencies, especially in the health sector. Hospitals have an important role in increasing human life expectancy, for this reason hospitals really need qualified civil servants.Civil servants in hospital must be superior and competitive human resources as shown by work discipline and high work motivation. The purpose of this study was to analyze the influence of work discipline and compensation variables on the performance of civil servants at Besuki Regional Hospital with work motivation as an intervening variable. This research is explanatory research. The population is in the study civil servants at Besuki Regional Hospital. The sampling technique used total sampling. Data analysis and hypothesis testing in this study used the Partial Least Square – Structural Equation Model (PLS-SEM). This resultof the direct influence hypothesis test using the Smart PLS 3.0 application showed that work discipline had a significant effect on work motivation, compensation had a significant effect on work motivation, work discipline had a significant effect on performance, and compensation was not proven to have a significant effect on performance. The result of indirect influence hypothesis test showed that the variable work discipline on performance through work motivation had a positive but not significant effect, compensation on performance through work motivation had a significant positive effect.